SOLUSI KREATIF PERMASALAHAN SAMPAH DI DESA JATIBARU KECAMATAN CIKARANG TIMUR - Sunita Dasman; Hamdan Ainul Yaqien (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Waste is still the main problem faced by the residents of Jatibaru village. The accumulation of garbage in several locations in Jatibaru village causes an unpleasant smell and becomes prone to disease. In addition, the scenery of Jatibaru village becomes unsightly to the eye. Public awareness and the absence of adequate landfill sites are problems with the accumulation of waste. This Ecobricks training aims to provide solutions to Jatibaru villagers to reduce the accumulation of plastic waste into a useful object. Ecobricks techniques are a practical and inexpensive solution to reduce plastic waste. The results of this training gave positive results to reduce the accumulation of plastic waste. However, there is a need for public awareness to sort plastic waste.